PRE-SERVICE ENGLISH TEACHERS’ PERSPECTIVES ON GAMIFICATION: A NEEDS ANALYSIS FOR GRAMMAR CLASS - Auliyanti Sahril Nurfadhilah; Muh Safar Nur; Dewi Atikah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
Grammar instruction in English as a Foreign Language (EFL) context is frequently perceived as anxiety-inducing and monotonous, particularly when learning is dominated by rule memorization and form-focused explanations. This issue is especially critical for pre-service English teachers, as their experiences as learners may influence their future teaching practices. Although gamification has been widely adopted to enhance engagement in grammar learning, many existing practices rely on surface-level mechanics such as points and quizzes, offering limited support for deep cognitive processing. To address this gap, this study conducted a needs analysis to examine pre-service English teachers’ perspectives on grammar instruction and their readiness for meaningful gamified learning. Employing a descriptive quantitative survey design, data were collected from 49 undergraduate students from English Education and English Literature programs who had completed grammar courses. The questionnaire explored grammar anxiety, digital readiness, flow potential, and gamification design preferences, and the data were analyzed using descriptive statistics. The findings reveal a moderate level of grammar anxiety and a notable gap between grammatical knowledge and its application in communication. At the same time, participants demonstrated high digital readiness and strong potential for immersive engagement. Importantly, they expressed a clear preference for deep, narrative-based gamification rather than quiz-oriented activities. These findings suggest that pre-service English teachers are cognitively and psychologically prepared for a deep-learning-oriented gamified grammar model, providing a foundation for future model development in teacher education contexts.Keywords: grammar anxiety, gamification, pre-service English teachers, needs analysis, grammar instruction